Pengaruh Pendidikan dan Pelatihan, Pengalaman Kerja, Kompetensi terhadap Kinerja Karyawan pada UKM di Bangkalan - Faidal, Faidal; Anshori, M Isa (BISMA (Bisnis dan Manajemen), 2018)
This research is to analyze the direct and indirect effect of human resource development to employee performance through the competence. This research was conducted at the SMEs sector in Bangkalan, Madura. There were 87 questionnaires that were able to be analyzed further from questionnaires distributed. Those data was analyzed by path analysis method. The result of data analysis showed that the education and training (X1) and working experience (X2) significantly gave direct influence to the competence (Z) each of them have 0.341 and 0.434. Moreover, the research also showed that education and training (X1) and working experience (X2) significantly had an effect on employee performance (Y) each of them have 0.486 and 0.472 directly and indirectly each of them have 0.263 and 0.335. At last, the effect of competence to the employee performance, showed that the competence (Z) significantly gave direct effect to the employee performance (Y) are 0.771 at the SMEs Bangkalan. There are two important implications from this research to the SMEs Bangkalan. Firstly, the implementation of the human resource development in order to increase the competence and the employee performance was optimal, therefore it should be continued and be maintained. Secondly, the improvement of the employee performance and the competence could be done by considering the effective implementation of human resource development.